Pengaru Penerapan Standar Akuntansi Pemerintah Kualitas Aparatur Pemerintahan Daerah dan Good Governance Terhadap Kualitas LaporanKeuangan (Studi Kasus Pada Dispenduk Kabupaten Belu Tahun 2021-2023) - Revalina Freitas Raimanis; Dwi Anggarani; Khojanah Hasan (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the influence of the implementation of Government Accounting Standards (SAP), the quality of local government officials, and the principles of good governance on the quality of financial statements at the Department of Population and Civil Registration (Dispendukcapil) of Belu Regency for the period 2021–2023. The quality of local government financial statements is highly important as a form of accountability and transparency in public financial management. The research method employed is quantitative with a survey approach. Data were obtained through the distribution of questionnaires to 41 respondents consisting of officials and employees directly involved in financial management. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25, including validity and reliability tests, classical assumption tests, and hypothesis testing using partial (t-test) and simultaneous (F-test) analyses. The results of the study indicate that, partially, the implementation of SAP, the quality of local government officials, and good governance have a positive and significant effect on the quality of financial statements. Among these three variables, good governance has the most dominant influence. Simultaneously, SAP, the quality of local government officials, and good governance significantly affect the quality of financial statements, with a coefficient of determination (R²) of 0.818, meaning that 81.8% of the variation in the quality of financial statements is explained by the three independent variables, while the remaining 18.2% is influenced by other factors outside this study. This study emphasizes that improving the quality of local government financial statements requires a combination of proper regulatory implementation, adequate competence of officials, and good as well as transparent governance.